Do we really understand accommodation preferences of visitors to the Kruger National Park? - Kruger, Martinette, author; van der Merwe, Peet, author; Slabbert, Elmarie, author; Saayman, Melville, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Accommodation plays such an important role in the tourist's experience, and one would imagine that many studies concerning this topic have been conducted. However, surprisingly very few studies have been carried out on this subject despite the growth in both demand and supply. This gap or lack of research led to the present exploratory study that addressed the question: what are visitors' accommodation preferences when they select accommodation in the Kruger National Park (KNP)? Based on a visitor survey in the Northern region of the Park during December 2015 where295 fully completed questionnaires were administered, respondents were segmented based on their accommodation preferences (self-serviced, serviced and safari). Three distinct clusters were identified, Self-service seekers, Service seekers, and Safari, service seekers. These clusters differ regarding their socio-demographic characteristics and especially regarding the factors they regard as important when selecting accommodation and campsites. This was the first time that the accommodation preferences of visitors to the flagship national park in South Africa were analysed. The results show that while visitors to the KNP appear homogeneous regarding their demographic profile, they differ significantly when it comes to accommodation needs and preferences. The findings from the research are valuable to park management especially when developing and expanding accommodation options in the park as it shows the preferences of each distinct market. This research furthermore makes a contribution to the current literature regarding ecotourism and ecotourists' accommodation preferences.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.